Book Review: Juxtaposition of K.H. Ahmad Dahlan and John Deweyâs Progressive Thoughts - MuÃ¢Â€Â™arif, MuÃ¢Â€Â™arif (Muhammadiyah University Press, 2017)
Book title : Paradigma Pendidikan Berkemajuan: Teori dan Praksis Pendidikan Progresif Religius KH Ahmad Dahlan AuthorÂ : Dr. Mohamad Ali, M.Pd. PagesÂ : xxxvi + 326 pages EditionÂ : I, October 2017 PublisherÂ : Suara Muhammadiyah